Made in Korea, remade in the Philippines the audience perception of Koreanovela remakes - Molina, Maritoni Benavides; Jazmines, Theresa M. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"This thesis examines the Filipino audience perception of Korean TV drama remakes produced in the Philippines from 2008 to 2011, the time when television programming in the country has shifted even more boldly to franchising and remaking foreign media content. Also produced at the time and space of the Korean cultural wave, Koreanovela remakes are attempts to recreate the success that has won the Filipino audience over. Employing both qualitative and quantitative methods, this research looks at the audience's consumption behavior, evaluation of program performance and experience of both Filipino and Korean culture, to determine their overall perception and learn whether or not the Koreanovela remakes succeeded in re-producing the same experience that the audience had with Korean TV dramas."
Thesis (A.B. Journalism)--University of the Philippines Diliman